2019
DOI: 10.32870/cys.v2019i0.7441
|View full text |Cite
|
Sign up to set email alerts
|

Análisis bibliométrico de estudios sobre la estrategia de contenidos de marca en los medios sociales

Abstract: Se analizan 106 estudios científicos, extraídos de Web of Science (WoS), sobre la estrategia de contenidos de marca en los medios sociales con el propósito de examinar el estado, la evolución y los diseños metodológicos del ámbito. Para ello se realiza un análisis bibliométrico cuantitativo y descriptivo. Los principales hallazgos son los indicios de madurez científica, como demuestran el predominio de estudios empíricos, la diversidad de actores, unidades de análisis y métodos de investigación, que facilitan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
4
0
5
Order By: Relevance
“…This review corroborates what was found in the systematic literature review on brand strategies in social networks carried out by Cuevas-Molano et al [41]. This study, in which the authors examined publications indexed in the Web of Science (WOS) over the last fourteen years, underlines the heterogeneity of the research carried out in this field.…”
Section: Customer Engagement In Social Networksupporting
confidence: 89%
“…This review corroborates what was found in the systematic literature review on brand strategies in social networks carried out by Cuevas-Molano et al [41]. This study, in which the authors examined publications indexed in the Web of Science (WOS) over the last fourteen years, underlines the heterogeneity of the research carried out in this field.…”
Section: Customer Engagement In Social Networksupporting
confidence: 89%
“…The advent of Web 2.0 and the development of ICTs have changed the way organizations communicate with their audiences [4], finding in social networks the ideal platforms to expand relationships beyond physical contact and install, or offer the possibility of doing so, other types of applications to attract and retain users [5]. Thanks to them, communication is now direct, two-way, and in real time.…”
Section: Social Media and Fashion Marketingmentioning
confidence: 99%
“…Previous researchs that relevant about bibliometric analysis on branding concept has been carried out, including 1) bibliometric analysis related to brand personality (Lara-Rodríguez et al, 2019), 2) bibliometric analysis related to artificial intelligence on branding (Novichkov et al, 2021), 3) bibliometric analysis of branding trends (Majerova et al, 2021), 4) bibliometric analysis of brand content strategy in social media (Cuevas-Molano et al, 2019), and 5) bibliometric analysis of the New Paradigm Of Branding In Social Media (Avasthi et al, 2021). From the previous research, we can conclude that the research has been published about branding almost in the context of bussiness, so it is an opportunity for us to discuss research trends about branding especially in the context of education.…”
Section: Introductionmentioning
confidence: 99%